The Measurement Model of Sosial Capital, Risk Taking and Sustainability in SMEs in West Sumatra - Yolanda, Fiska; Masdupi, Erni (Universitas Negeri Padang, 2023)
This study provides evidence of a measurement model (confirmatory factor analysis–CFA) of sustainability, sosial capital and risk taking. UKM in West Sumatra in 2023. The purpose of this research is to test the accuracy of the measurement model on the data thas has been collected. To answer this research question using a structural equation model (SEM), with a sample of 250 SMEs. The resulting data analysis found that the hypothesized model is valid and significant. The sustainability indicator has a significant factor loading and is more than 0,3. With the highest loading standard on the sixth indicator of 0,876, and the lowest loading standard on the third indicator of 0,445. The sosial capital indicators have all significant factor loadings and are more than 0,3. The highest loading standard is the seventh indicator of 0,886 and the lowest is the fourth indicator of 0,401. Risk taking also has a factor loading of all significant indicators and more than 0,3. With the highest loading standard located on the first indicator of 0,930, and the lowest loading standard on the fifth indicator, namely 0,582.